ANALISIS PENGARUH KEMAMPUAN PENGAWAK TERHADAP KUALITAS LAYANAN MEDIS PADA KAPAL TNI AL - Agung Nugroho; Edi Riesnandar (Faculty of Science and Technology University of Pramita Indonesia, 2023)
Optimal quality of medical services is very important in ensuring the health and welfare of military personnel on board the Indonesian Navy. This study aims to gain a better understanding of the factors that influence the quality of medical services in the maritime environment and to analyze the effect of crew capabilities on the quality of medical services on Indonesian Navy ships. A quantitative research approach by collecting data from medical crew and medical patients being treated on board the Indonesian Navy. The research instrument was a questionnaire designed to measure the ability of crew members and patient perceptions of the quality of medical services. The results showed that there was a positive relationship between the crew's ability and the quality of medical services on Indonesian Navy ships, where statistical analysis showed that the higher the crew's ability, the higher the quality of medical services provided. In addition, patient perceptions of the quality of medical services also have a significant impact on the overall assessment of medical services. Based on the results of this study, it was concluded that the ability of medical crew plays an important role in determining the quality of medical services on Indonesian Navy ships, as well as the importance of developing the capabilities of medical crew and the need to focus on certain aspects in improving the quality of medical services in the maritime environment.